Excess of exercise increases the risk of atrial fibrillation. (16th January 2017) - Müssigbrodt, A.; Weber, A.; Mandrola, J.; van Belle, Y.; Richter, S.; Döring, M.; Arya, A.; Sommer, P.; Bollmann, A.; Hindricks, G.
Abstract : An interesting and still not well‐understood example for old medical wisdom "Sola dosis facit venenum" is the increased prevalence of atrial fibrillation (AF) in athletes. Numerous studies have shown a fourfold to eightfold increased risk of AF in athletes compared to the normal population. Analysis of the existing data suggests a dose‐dependent effect of exercise. Moderate exercise seems to have a protective effect and decreases the risk of AF, whereas excessive exercise seems to increase the risk of AF. The described cases illustrate clinical manifestations within the spectrum of AF in elderly athletes, that is, exercise‐induced AF, vagal AF, chronic AF, and atrial flutter. As the arrhythmia worsened quality of life and exercise capacity in all patients, recovery of sinus rhythm was desired in all described cases. As the atrial disease was advanced on different levels, different treatment regimes were applied. Lifestyle modification and temporary anti‐arrhythmic drug therapy could stabilize sinus rhythm in one patient, whereas others needed radiofrequency ablation to achieve a stable sinus rhythm. The patient with the most advanced atrial disease necessitated anti‐arrhythmic drug therapy and another left atrial ablation. All described patients remained in sinus rhythm during the long‐term follow‐up.